Judging the Conducător: fascism, communism and legal discontinuity in post-war Romania - Cercel, Cosmin Sebastian (Cambridge University Press, 2016)
The proposed chapter aims to further the engagement with the past by bringing to the fore the legal and memorial dynamics at work in the post war trials dealing with Romanian participation to the Holocaust. While work in this area of Romanian legal history is still exploratory, this chapter aims at filling a gap in relation to understanding the constitutional, jurisprudential and ideological aspects of the Antonescu trial. In doing so it also aims to reflect on the legal, political and symbolic consequences entailed by the communist attempts at dealing with Romanian participation to the Holocaust. In this sense, this chapter attempts for the first time to articulate jurisprudentially and historically the significance of the trial of the Romanian military dictator in office between 1940 and 1944.